2017
DOI: 10.1007/s11060-017-2607-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of glioma: clinical characteristics, symptoms, and predictors of glioma patients grade I–IV in the the Danish Neuro-Oncology Registry

Abstract: In this national population-based study of glioma, we present epidemiologic data on incidence, demographics, survival, clinical characteristics and symptoms, and evaluate the association of specific indicators with the grade of glioma. We included 1930 patients registered in the Danish Neuro-Oncology Registry (DNOR) from 2009 to 2014. DNOR is a large-scale national population-based database including all adult glioma patients in Denmark. The age-adjusted annual incidence of histologic verified glioma was 7.3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
126
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 35 publications
12
126
1
3
Order By: Relevance
“…It is more prevalent in males compared to females. Incidence of high-grade glioma tends to increase with age (Louis et al, 2016;Rasmussen et al, 2017;Ostrom et al, 2018). This was also described in our study with male patient predominance (male: female = 1.26: 1), the youngest mean age was in glioma grade I (14.71 years old) while the highest mean age was in grade IV (46.50 years old) and the most common diagnosis was Glioblastoma, IDH-wildtype, (31.13%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more prevalent in males compared to females. Incidence of high-grade glioma tends to increase with age (Louis et al, 2016;Rasmussen et al, 2017;Ostrom et al, 2018). This was also described in our study with male patient predominance (male: female = 1.26: 1), the youngest mean age was in glioma grade I (14.71 years old) while the highest mean age was in grade IV (46.50 years old) and the most common diagnosis was Glioblastoma, IDH-wildtype, (31.13%).…”
Section: Discussionmentioning
confidence: 99%
“…Data from The Global Cancer Atlas showed that 5.323 people i n Indonesia were diagnosed with primary brain and central nervous system cancer in 2018. Gliomas are the most frequent among all primary brain tumors (Rasmussen et al, 2017;Bray et al, 2018). Glioma histological grading classification based on World Health Organization (WHO) was divided into 4 grades (grade I-IV).…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved; however, as shown in Table only a minor variation was achieved concerning the age difference. Still, this was anticipated as gliomas occur most frequently between 58–78 years of age (Rasmussen et al., ).…”
Section: Participants and Settingmentioning
confidence: 99%
“…5 Common symptoms and side effects include seizure, nausea and vomiting, and headache. [6][7][8] To address the neurologic symptoms associated with glioma, patients are often prescribed glucocorticoids (levetiracetam followed by lacosamide or valproic acid are agents of choice); however, long-term steroid use may have adverse effects. 9 While standard management for grade III-IV tumorsmaximal safe resection followed by chemoradiation 10 -may be associated with temporary amelioration of symptoms, the majority of patients suffer declining functional and cognitive status as the tumor progresses.…”
Section: Introductionmentioning
confidence: 99%